Cover. (25th March 2018) - Gomez‐Lopez, Nardhy; Romero, Roberto; Xu, Yi; Miller, Derek; Leng, Yaozhu; Panaitescu, Bogdan; Silva, Pablo; Faro, Jonathan; Alhousseini, Ali; Gill, Navleen; Hassan, Sonia S; Hsu, Chaur‐Dong
Abstract : Front cover : The cover image, by Nardhy Gomez‐Lopez et al., is based on the Original Article The immunophenotype of amniotic fluid leukocytes in normal and complicated pregnancies, DOI:10.1111/aji.12827